Academic administration factors affecting blended learning system for colleges in Henan province - Chen, Xudong; Siththada, Thada; Boonphadung, Suttipong (Edelweiss Applied Science and Technology, 2025)
This study investigates academic administration factors affecting the implementation of blended learning systems in colleges across Henan Province, China. Blended learning, which integrates face-to-face instruction with online components, is gaining traction as a flexible and personalized educational approach. However, challenges such as faculty preparedness, resource disparities, and system inconsistencies necessitate robust administrative strategies. Using a mixed-methods design, the study surveyed 502 teachers and administrators across 60 colleges and conducted semi-structured interviews with nine experts. Quantitative analysis revealed moderate overall levels of academic administration factors (M=3.49) and blended learning systems (M=3.54). Learning participation (M=3.63) and teaching methods (M=3.59) were rated highest, while teacher evaluation (M=3.24) and external environment (M=3.28) scored lowest. Regression analysis identified teaching effectiveness (β=0.24) and learning participation (β=0.42) as key predictors, explaining 65% of the variance in the learning system. Qualitative findings highlighted infrastructure disparities, faculty training gaps, and overreliance on summative assessments. Recommendations include upgrading technological infrastructure, implementing faculty development programs, and redesigning assessment systems to enhance equity and learning quality. The study contributes to blended learning literature by contextualizing these challenges within Henan’s educational landscape and offers actionable guidelines for improving system effectiveness.